2018
DOI: 10.1111/bjdp.12271
|View full text |Cite
|
Sign up to set email alerts
|

Language development and intelligence in midlife

Abstract: Individual differences in early language skills have been found to be associated with other cognitive outcomes in childhood and adolescence. However, research is limited on whether these associations persist into adulthood. In this study, we examined potential associations of the timing of early language milestones with cognitive ability in a prospective cohort study of 938 singletons from the Copenhagen Perinatal Cohort (CPC), who participated in a 50‐year follow‐up examination in 2009–2011. Later attainment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
8
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to investigate associations between the timing of early language development and personality in midlife. However, a previous study based on the same birth cohort found significant associations between faster language development and intelligence in midlife (Flensborg-Madsen & Mortensen, 2018c), which may support our results on associations between language development and openness to experience as high correlations are often found between intelligence and openness (Matthews, Deary, & Whiteman, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study to investigate associations between the timing of early language development and personality in midlife. However, a previous study based on the same birth cohort found significant associations between faster language development and intelligence in midlife (Flensborg-Madsen & Mortensen, 2018c), which may support our results on associations between language development and openness to experience as high correlations are often found between intelligence and openness (Matthews, Deary, & Whiteman, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…All variables were included as linear continuous variables except for parity (included as a binary variable indicating first or later pregnancy), smoking (included as a binary yes/no variable), and sex. Additionally, we included intelligence as a covariate in supplementary analyses (Online Supplemental Tables S1 and S2) as intelligence has been found to be associated with both language milestones (Flensborg-Madsen & Mortensen, 2018a, 2018b, 2018c) and personality (Flensborg-Madsen & Mortensen, 2014). Assessments of intelligence were based on Wechsler’s Adult Intelligence Scale (Wechsler, 1958) at the PDP follow-up and the Intelligenz-Struktur-Test 2000 R (Amthauer, Brocke, Liepman, & Beauducel, 2001) at the CAMB follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parental social status is in this study defined as a joint measure of both educational and occupational aspects as well as the character of the living accommodation, and the results are therefore in accordance with previous studies showing that socioeconomic status [23] and maternal education [2426] are positively associated with language development, in particular since we observed the strongest association for milestones related to Language. Cognitive and language development are closely related, and in the Copenhagen Perinatal Cohort (CPC), language milestones predict young adult and midlife intelligence [16, 45]. Since the CPC measure of parental social status is a strong predictor of offspring adult intelligence [46], a relatively strong association between parental social status and Language milestones was expected, but the strength of the association was considerably weaker than the association between sex and Language milestones.…”
Section: Discussionmentioning
confidence: 99%